Policy professionals in Danish think tanks: education, professional experience and visibility in the Parliament and omnibus newspapers - Kelstrup, Jesper Dahl (Politica, 2020)
How do the educational backgrounds and work experiences of policy professionals contribute to the visibility of Danish think tanks in Parliament (Folketinget) and in omnibus newspapers? An analysis of 126 policy professionals employed in ten privately funded think tanks indicates that most policy professionals hold social science degrees and have prior work experience from the public sector, interest organizations and the private sector. Some advocacy think tanks hire many economists, and the proportion of employees with a Master’s degree in economics correlates positively with both mentions in Parliament and the visibility of think tanks in Danish newspapers. On this basis, more research on why and under what circumstances economists are particularly apt at contributing to the public visibility of think tanks should be undertaken.